Designing King Al Post As English Teaching Media For Beginner Students - Anisa -; Iin Baroroh Ma'arif; Ulfa Wulan Agustina (Universitas KH. A. Wahab Hasbullah, 2018)
Technology has grown rapidly in education sector, it creates new opportunities for improving learning experience of students at any levels of education. One of them is education in Junior high school. Teaching them will be interested and completely different, because beginners are unique and are able to think abstractly and logically. Therefore, the researcher aimed to design English learning media for beginner students as a media that were appropriate for their learning needs. There were two research objectives; these are desingning King Al PoST and knowing the feasibility of the English learning media. the researcher uses Research and Development method adapted from Borg and Gall’s development. This English learning media were validated by material expert and media expert before trying to the students. While, the instrument of this research are questionnaires and interviews to material expert, media expert, and students. The result of this research showed that 1) the result of material expert is 85 score; 2) the result of media expert is 85,00 score; 3) the result of preliminary field testing is 88,67 score; 4) the result of operational field testing is 90,25. Based on the result above, the researcher conclude that King Al PoST is feasible to use in English learning. From the result there were two suggestions: 1) to the English teacher it can be used to be alternative teaching media to teach English; 2) to the other researcher it can be used to do the research at different level of the students.